Kultur Campuran dan Faktor Lingkungan Mikroorganisme yang Berperan dalam Fermentasi âTea-Ciderâ - Pingkan Aditiwati; Kusnadi Kusnadi (Journal of Mathematical and Fundamental Sciences, 2003)
Tea is agricultural product containing beneficial substances, especially used for human health. The study of "Tea-cider" fermentation has been conducted using batch culture method. The purposes of the study were to observe mixed microbial culture which were actively involved in the process of "Tea-cider" fermentation, to determine the optimum fermentation conditions, as well as to evaluate the inhibition effect of the product against pathogenic bacteria. The study was carried out in two steps. Firstly, the isolation of microorganisms from "Tea-cider"; secondly producing "Tea-cider" using mixed microbial culture isolated from "Tea-cider" and "Tea-cider" itself as inoculum. Type and concentration of inoculum were optimized for the fermentation process. Mixed of the pure culture of isolated microorganisms with variation of initial cell at ratio B : K1 : K2 = 1 : 1 : 1, 3 : 1 : 1 and 5 : 1 : 1 while the variation of inoculum were 5%, 10%, and 15% (v/v). Optimization in temperature, pH and sugar concentration at the variation of temperature 250C, 280C, 300C, and 350C, pH of 4, 5, and 6, and sugar concentration 5%, 10%, and 15% (w/v) respectively. The pH, acid concentration, reducing sugar concentration and alcohol concentration were analized at 48 hours interval during 14 days fermentation. The product was tested for antimicrobial effect using agar diffusion method and for organoleptic. The result showed that mixed microbial culture which were actively involved in "Tea-cider" fermentation were yeast Schizosaccharomyces pombe (K1) dan Brettanomyces sp (K2), and a species af aceticacid Acetobacter xylinum (B). The optimum condition of "Tea-cider" fermentation were as follows, the ratio of B : K1 : K2 optimum mixed culture inoculum at 5 : 1 : 1 and 10% (v/v) for the inoculum. The incubation temperature was 300C, the medium initial pH was 5 and the intial sugar concentration was 10% (w/v). The "Tea-cider" product was able to inhibit the growth of some pathogenic bacteria such as Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli and had a good preferred taste.